x+x(.50-.60)=450

Simple and best practice solution for x+x(.50-.60)=450 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+x(.50-.60)=450 equation:


Simplifying
x + x(0.50 + -0.60) = 450

Combine like terms: 0.50 + -0.60 = -0.1
x + x(-0.1) = 450

Reorder the terms for easier multiplication:
x + -0.1x = 450

Combine like terms: x + -0.1x = 0.9x
0.9x = 450

Solving
0.9x = 450

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '0.9'.
x = 500

Simplifying
x = 500

See similar equations:

| 6y+y^2=4 | | 5n=21+4b | | 6y+y^2=6 | | 9-3/8 | | 6(2x-8)+3=14 | | 9^3x*8^2x=1/36 | | 2/3=x/2+1/4 | | (q+4)(q-6)= | | 8x+5x=52 | | x-(2-x)=-2(2x-4) | | 9z^2-9z-9=0 | | y^2=y+12 | | n/6+48=62 | | 20+8x-5=8x+21 | | 8000+8000(.20-x)=7200 | | 59=7+4m | | 10x-5=25whatx | | -5x^2+450x-10000=0 | | -5x-3y=12 | | -10y+18=-15y-2+5y | | 5x+10-10=30 | | x^2-5xy+y^2=4 | | 3x-6=6x-36 | | 11x+16=6x+81 | | (2y+1)/4=(y-3)/3 | | (2y+1)/4=(y-3)/3 | | 4x/2x^2 | | 7k-(9k-16)=14-(19-k) | | x^2+xy=5 | | 8x-4=17+x | | ax-7a=1 | | 0.6-50y=3 |

Equations solver categories